Value-added Tax versus Social Security Contributions - Laszlo Goerke (Institute for the Study of Labor (IZA), 1999)
In order to alleviate unemployment it is often recommended to reduce social security contributions (SSC) and to compensate for the ensuing loss in revenues by a rise in the value-added tax (VAT). Assuming unemployment to be caused by efficiency wages, it is shown that a balanced-budget shift from a payroll tax to a VAT will increase employment if the rise in the VAT does not alter consumer prices. If the effects of a shift from SSC to the VAT on the worker's effort are neutralised, for example, by imposing a constant wedge, the employment impact will depend on the nature of the unemployment compensation system.
Keywords: H25; J41; J32; H24; 330; Efficiency wages; social security contributions; unemployment; value-added tax; Beschäftigungspolitik; Sozialversicherungsbeitrag; Umsatzsteuer; Personalzusatzkosten; Effizienzlohn; Arbeitslosigkeit; Beschäftigungseffekt; Theorie